The Arabs are alive - Sardar, Ziauddin; Yassin-Kassab, Robin (Critical Muslim, 2010)
In the inaugural issue of Critical Muslim: Ziauddin Sardar tries to understand the significance of what just happened in the Middle East, Robin Yassin-Kassab spends some quality time in Tahrir Square, Ashur Shamis dodges the bullets of Gaddafi's henchmen, Abdelwahab El-Affendi traces the roots of the uprisings, Anne Alexander tunes into the digital revolution, Fadia Faqir joins women protestors, Shadia Safwan asks how long could Assad last, Jamal Mahjoub contemplates futures of the Sudan, Jasmin Ramsey joins the activists in Tehran, and Jerry Ravetz ponders the significance of Ibn Khaldun to the Arab Spring. Also in this issue: Rachel Holmes visits the Palestinian Festival of Literature, S. Parvez Manzoor asks if Turkey is a good model for the Muslim world, Muhammad Idrees Ahmad is overwhelmed by leaks, Taus Makhacheva takes 'Affirmative Action', Aasia Nasir accuses Pakistan and Merryl Wyn Davies's 'last word' on Saudi women drivers. Plus a new short story from Bilal Tanweer and revolutionary poetry from Nizar Qabbani, Tawfiq Zayyad, Abul-Qasim al-Shabi, Ayat al-Qormezi and Naomi Foyle.